2006
DOI: 10.1593/neo.05697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extracellular Acidity on the Activity of P-glycoprotein and the Cytotoxicity of Chemotherapeutic Drugs

Abstract: The expression and activity of P-glycoprotein (pGP) play a role in the multidrug resistance of tumors. Because solid-growing tumors often show pronounced hypoxia or extracellular acidosis, this study attempted to analyze the impact of an acidic environment on the expression and activity of pGP and on the cytotoxicity of chemotherapeutic agents. For this, prostate carcinoma cells were exposed to an acidic extracellular environment (pH 6.6) for up to 24 hours. pGP activity was more than doubled after 3 to 6 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 40 publications
6
134
0
1
Order By: Relevance
“…Raghunand et al (1999) reported that the extracellular pH of human breast tumor is acidic, which reduces the cytotoxicity of doxorubicin [17]. Thews et al (2006) showed that acidic extracellular microenvironment can induce activity of p-glycoprotein which leads to reduce the concentration and cytotoxicity of chemotherapeutic drug by pumping entered drug to outside [41]. Lan et al (2007) demonstrated microenvironmental pH can control the type of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Raghunand et al (1999) reported that the extracellular pH of human breast tumor is acidic, which reduces the cytotoxicity of doxorubicin [17]. Thews et al (2006) showed that acidic extracellular microenvironment can induce activity of p-glycoprotein which leads to reduce the concentration and cytotoxicity of chemotherapeutic drug by pumping entered drug to outside [41]. Lan et al (2007) demonstrated microenvironmental pH can control the type of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it is of a great importance the ability of acidic pH e to increase the pump activity of the p-glycoprotein (pGP), a drug efflux transporter. Thews et al observed that acidic prostate carcinoma cells express a pGP activity more than doubled of that of cells grown in a standard pH medium [107]. These authors reported that up-regulation of pGP in acidic cells was related to an increased intracellular Ca 2+ level, stimulated by a protein kinase C activity [107].…”
Section: Acidity Promotes Resistance To Drug and Radio-treatmentmentioning
confidence: 99%
“…Thews et al observed that acidic prostate carcinoma cells express a pGP activity more than doubled of that of cells grown in a standard pH medium [107]. These authors reported that up-regulation of pGP in acidic cells was related to an increased intracellular Ca 2+ level, stimulated by a protein kinase C activity [107]. It has also been observed that acidosis-induced pGP activity may be related to ERK and p38 pathways.…”
Section: Acidity Promotes Resistance To Drug and Radio-treatmentmentioning
confidence: 99%
“…Stresses-Abundant evidence confirms that extracellular acidity has a positive effect on the survival and malignant potential of many cancer cells (5,6,31). Although more intensively studied in solid tumors, acidosis is known to occur in the microenvironment of hematologic malignancies as well (3).…”
Section: Acidosis Protects Against Multiple Cytotoxic Metabolicmentioning
confidence: 99%